(untitled) (KULT_online, 2011)
The discovery of America in 1492, of the sea route to India in 1498, and the first circumnavigation of the globe in 1522 are considered to be the beginning of globalization, even though the term itself wasn’t coined until much later, namely until the 20th century. Davide Scruzzi earned his PhD analysing the shift of spaces perceived by the Venetians, and in which spaces they act after geographic discoveries. He uses letters, official reports, diaries, maps, and chronicles to reconstruct cognitive maps and show how Venice, whose main trade room at that time was the Mediterranean, reacted towards these new geographic conditions.